MANAJEMEN PENERIMAAN SANTRI BARU DI PONDOK PESANTREN DARUL ITTIHAD KABUPATEN KAMPAR PROVINSI RIAU TAHUN 2024 - Aan Budiyono; Siti Patimah; Nur Hidayah; A. Lathief Arung Arafah (Program Studi Manajemen Pendidikan Islam, 2025)
This study aims to determine how the management of admission of new students at Darul Ittihad Boarding School Kampar Regency, Riau Province. The research method used is descriptive method using a qualitative approach. The techniques used in data collection are observation, interview, and documentation. Data were obtained from observations and interviews with the subjects of this study, namely the head of the islamic boarding school, the chairman of the new student admission committee, and several new student admission committee members at Darul Ittihad Boarding School Kampar Regency, Riau Province. The results of this study indicate that, the management activities of new student admission include the admission planning process and the implementation of new student admission. The process of implementing new student admission activities at Darul Ittihad Boarding School Kampar Regency, Riau Province includes: a) Formation of the New Student Admission Committee. b) Meeting of the New Student Admission Committee. c) Making and installing admission announcements. d) Registration Process. e) Selection. f) Determination of accepted students. g) Announcement of accepted students. h) Re-registration i) New Student Orientation (Matsaba) and the last process, namely; j) Evalution